1987
DOI: 10.1073/pnas.84.22.7925
|View full text |Cite
|
Sign up to set email alerts
|

Lignin degradation by peroxidase in organic media: A reassessment

Abstract: The effect of horseradish peroxidase/H202 in organic medium (dioxane/aqueous buffer, pH 5, 95:5) on the depolymerization of synthetic (dehydrogenatively polymerized) lignin was reinvestigated. In contrast to previous claims [Dordick, J. S., Marietta, M. A. & Klibanov, A. M. (1986) Proc. Natl. Acad. Sci. USA 83, 6255-6257], our results demonstrated that vigorous depolymerization of this substrate did not occur. Further, during this treatment ferulic acid was not a significant biodegradation product.It is well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Using GC-MS according to Lapierre [31], Table 4 also shows a preferential relative decrease in /3-5 and /3-1 dimeric units as compared to the relative changes in 5-5' and 4-0-5' units, suggesting a higher susceptibility of these dimeric structure to enzymatic oxidation, the mechanism of which remains unknown. Whatever the differences and even when gel permeation experiments did not allow to demonstrate any biomimetic degradation by HRP, in agreement with Lewis et al [26], Table 4 allows to conclude that HRP also exhibits ligninolytic properties, in agreement with Dordick et al [27].…”
Section: A Case Study: Peroxidase Degradation Of Spruce Ligninsupporting
confidence: 88%
See 1 more Smart Citation
“…Using GC-MS according to Lapierre [31], Table 4 also shows a preferential relative decrease in /3-5 and /3-1 dimeric units as compared to the relative changes in 5-5' and 4-0-5' units, suggesting a higher susceptibility of these dimeric structure to enzymatic oxidation, the mechanism of which remains unknown. Whatever the differences and even when gel permeation experiments did not allow to demonstrate any biomimetic degradation by HRP, in agreement with Lewis et al [26], Table 4 allows to conclude that HRP also exhibits ligninolytic properties, in agreement with Dordick et al [27].…”
Section: A Case Study: Peroxidase Degradation Of Spruce Ligninsupporting
confidence: 88%
“…For example, a plant peroxidase from horseradish has been reported to vigorously depolymerize milled wood lignin in organic solvent containing few percent of aqueous buffer while being unable, however, to degrade lignins in aqueous solution [25]. Later on, this statement however has been reassessed by Lewis et al [26] who, in contrast to these previous claims, reported that vigourous depolymerization of synthetic lignin (DHP: dehydrogenatively polymerized) did not occur in aqueous organic media.…”
Section: A Case Study: Peroxidase Degradation Of Spruce Ligninmentioning
confidence: 99%
“…The breakdown of lignin by peroxidase in non-polar solvents forming quantities of compounds such as ferotic acid and vanillin was described by . However, Lewis et al (1987) could not repeat these results and there have been no further claims in this area to date.…”
Section: Ligninmentioning
confidence: 89%
“…It has been suggested that peroxidases can depolymerize lignin more effectively in non-aqueous solvents (Dordick et al 1986). If this is indeed the case (Lewis et al 1987), it has relevance to the technological exploitation of lignin peroxidases and lignins. 7.…”
Section: The Phanerochaete Chrysosporium Lignin Degradation Systemmentioning
confidence: 99%